2004
DOI: 10.1309/brn7ctx1e84nwwpl
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Mechanism of Formalin Fixation and Antigen Retrieval

Abstract: Despite the popularity of antigen-retrieval techniques, the precise molecular mechanism underlying the process remains enigmatic. We examined the molecular features underlying the loss of immunoreactivity following formalin fixation, with subsequent recovery by antigen retrieval. To do this, we first created a molecular model using short peptides that mimic the antibody-binding site of common clinical protein targets. The advantage of this model is that we know the amino acid sequence in and around the antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
59
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(61 citation statements)
references
References 0 publications
1
59
0
Order By: Relevance
“…22 So far, the mechanisms of crosslinking reversal as the base for antigen retrieval are not well understood. [23][24][25] Elucidation of these mechanisms will be very helpful for optimization of macromolecular extraction. Current methods for antigen retrieval include proteinase predigestion, 26 chemical pretreatment, [27][28] and heat-induced epitope retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…22 So far, the mechanisms of crosslinking reversal as the base for antigen retrieval are not well understood. [23][24][25] Elucidation of these mechanisms will be very helpful for optimization of macromolecular extraction. Current methods for antigen retrieval include proteinase predigestion, 26 chemical pretreatment, [27][28] and heat-induced epitope retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Ready-to-use assays offer improved reproducibility and consistency, minimizing effects arising from reagent diversity, as well as variability that can arise from antigen retrieval. [8][9][10][11][12][13][14][15][16] Surprisingly, these platform-specific ready-to-use assays have never been directly compared using the same clinical outcome series.…”
mentioning
confidence: 99%
“…Sompuram and colleagues concluded that the Mannich reaction may play an important role in this process [13]. This reaction…”
Section: Discussionmentioning
confidence: 99%